Microbial diversity and digestive enzyme activities in the gut of earthworms found in sawmill industries in Abeokuta, Nigeria - Bamidele, Julius A; Adewunmi B., Idowu; Kehinde O., Ademolu; Adijat O., Atayese (Revista de Biología Tropical, 2014)
The growing demand for wood has resulted in large volumes of wood wastes that are daily released to the soil from the activities of sawmills in South-Western Nigeria. In an attempt to setup a bioremediation model for sawdust, this study therefore aimed at evaluating microbial diversity, and the level of digestive enzymes in the gut of earthworms (Eudrilus eugeniae, Libyodrilus violaceous and Hyperiodrilus africanus) of sawmill origin. Four major sawmills located in Abeokuta (7o9'12" N - 3o19'35" E), namely Lafenwa, Sapon, Isale-Ake and Kotopo sawmills were used for this study. The arboretum of the Federal University of Agriculture, Abeokuta was used as control. Gut microbial analysis was carried out using the pour-plate method while digestive enzyme activities in the earthworm guts were done by the spectrophotometric method. Higher microbial counts (28.5±0.1x103-97.0±0.1x103cfu for bacteria and 7.0±0.1x103-96.0±0.1x103cfu for fungi) and microbial diversity were recorded in the gut of earthworms of the sawmill locations than those of the control site (17.5±0.1x103cfu for bacteria and 4.5±0.1x103cfu for fungi). Streptococcus mutans and Proteus spp. were common in the gut of E. eugeniae, and L. violaceous from the study sawmills, while Streptococcus mutans were also identified in H. africanus, but absent in the gut of E. eugeniae from the control site. Cellulase (48.67±0.02mg/g) and lipase (1.81±0.01mg/g) activities were significantly higher (p<0.05) in the gut of earthworms from the control site than those of the study sawmills. Furthermore, amylase (α and β) activity was highest in the gut of earthworms from the sawmills. Variations observed in the gut microbial and digestive enzyme activities of earthworms from the study sawmills as compared to the control site suggests that earthworms, especially E. eugeniae, could be a better organism for use as bioremediator of wood wastes.